Okul Öncesi Öğretmenlerinin Derslerinde Kullandıkları Öğretim Yöntem Ve Tekniklere İlişkin Görüşleri. - Bulut, Ayhan (Electronic Turkish Studies, 2020)
This research aims to determine preschool teachers' views on teaching methods and techniques used in implementing educational activities in learning and teaching process and the problems they face while performing these practices. The population of the study consists of preschool teachers working in the central districts of Erzurum. In addition, typical sampling method was used in this study. Since the universe is very large, 45 preschool teachers who were working in the 2018/2019 academic year and willing to support the research voluntarily were selected as the sample with the typical case sampling method. The research process is designed in the case study pattern of qualitative research methods. Content analysis and descriptive analysis were used to analyze the data. According to the results of the research, it was stated that the most commonly used teaching methods and techniques used by preschool teachers to implement activities in the learning process were to show and have them done. On the other hand, preschool teachers stated that children mostly pay attention to the readiness levels when choosing the teaching methods and techniques used in the activities. They also stated that the teaching methods and techniques used in the learning process facilitate learning for themselves. However, preschool teachers stated that the most crowded classrooms and the resulting distractions in children were most influenced when choosing the teaching methods and techniques used in implementing the activities in the learning process. Because of these reasons, they stated that they had time difficulties in implementing some activities.